Characteristics and experiences of interns in strength and conditioning. Issue 3 (1st February 2017) - Read, Paul; Hughes, Jonathan D.; Blagrove, Richard; Jeffreys, Ian; Edwards, Mike; Turner, Anthony N.
ABSTRACT: Student coaches undertake internships to develop practical skills and gain experience to improve employability prospects. The characteristics of the coaches who undertake these internships, their experiences and the nature of the work being performed are currently unknown. The purpose of this study was to report the characteristics of strength and conditioning (S&C) coaches who have undertaken internships and their experiences during their respective placements. A total of 113 men and 6 women completed an online survey. Placements generally lasted 6–12 months (66%), were unpaid (93%) and took place at professional teams (63%). All respondents had a standard of experience prior to commencement (82%); a higher-education degree (bachelor's degree 56%; master's degree 18%) and others were qualified S&C coaches (16%). Activities consisted largely of coaching (47%), data collection (22%) and equipment set-up (25%) but lacked provision of appropriate training. Mentors were allocated to interns; however, often developmental objectives were not discussed, meetings were rarely documented, and in some cases, no meetings took place. This study suggests that internships offer worthwhile experiences and assistance in skill development to progress in S&C. However, clearer guidelines are required to define the responsibilities of employers and interns, to maximise these experiential learning opportunities and avoid the exploitation of willing students.